2009
DOI: 10.1016/j.jad.2008.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive inhibition and working memory in unipolar depression

Abstract: Depressed patients showed inability to inhibit neutral information access to working memory, restrain and delete irrelevant information. This impairment in cognitive inhibition could underlie cognitive slowness and attentional deficits in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
120
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(135 citation statements)
references
References 28 publications
12
120
1
2
Order By: Relevance
“…As in previous studies, there were no significant differences in execution time (cognitive slowness) between depressive subjects and healthy controls (Gohier et al, 2009), despite the first having exhibited a slower performance.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As in previous studies, there were no significant differences in execution time (cognitive slowness) between depressive subjects and healthy controls (Gohier et al, 2009), despite the first having exhibited a slower performance.…”
Section: Discussionsupporting
confidence: 80%
“…Alterations in execution time (Gohier et al, 2009), as well as in interference (Harvey et al, 2004;Stordal et al, 2004), are common in depression. Concerning unipolar depressed patients, rostral anterior cingulate gyrus (rACG) and left dorsolateral prefrontal cortex (DLPFC) is involved in interference (Wagner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor performance on the DSST and DVT i.e., 30% and 32% respectively, and poorer performance on the Stroop test in the present sample is in line with existing literature (14,15,16,17). But some other studies have reported no difference in performance of executive functions between depressed and control groups (18,19).…”
Section: Discussionsupporting
confidence: 91%
“…Over the past decade, evidence has accumulated to suggest that patients with depression were significantly impaired on tasks of attention, executive function, memory and psychomotor speed. These findings suggest deficits in cognitive function, attention, visual and verbal memory and learning, as vulnerability marker for major depressive disorder (Channon & Green, 1999;Gohier et al, 2009;Weingartner et al, 1981).…”
Section: Introductionmentioning
confidence: 81%